Introduction to the American Studies Bibliography: Hungarian Contributions Project - Kovács, Ágnes Zsófia; Szélpál, Lívia (AMERICANA E-journal of American Studies in Hungary, 2023)
Introduction to the American Studies Bibliography: Hungarian Contributions Project